Análisis termodinámico de un ciclo rankine orgánico usando biogás generado por digestión anaerobia de residuos de cosecha de banano (2024)
This degree work was carried out to evaluate the viability of producing electrical energy with an Organic Rankine Cycle in non-interconnected areas of Colombia. The above using biogas as fuel, a product of the Anaerobic Digestion of Banana Harvest Residues. For this, an Organic Rankine Cycle was designed and simulated using the EES software, measuring its performance through an energy and exergy balance. The Organic Rankine Cycle was designed for an available heat of 11.62 kW, taking into account that the biomass had a biogas yield of 271 ml/kg ST. The designed CRO generates 1.48 kW of electrical energy with an efficiency of 12.2%. This was designed from the waste of a 3.5 ha banana plantation, and can generate 12,999 kWh annually. Several exergy parameters were analyzed and the exergy efficiency of the cycle was 66.37%, where the boiler and the condenser are the equipment with the highest exergy destruction.